2008
DOI: 10.1088/1126-6708/2008/08/010
|View full text |Cite
|
Sign up to set email alerts
|

Holographic double diffractive scattering

Abstract: The holographic description of Pomeron exchange in a strongly-coupled gauge theory with an AdS dual is extended to the case of two to three scattering. We study the production event of a central particle via hadron-hadron scattering in the double Regge kinematic regime of large center-of-momentum energy and fixed momentum transfer. The computation reduces to the overlap of a holographic wave function for the central particle with a source function for the Pomerons. The formalism is applied to scalar glueball p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…This argument has been extended to near-forward QCD scattering in AdS/CFT. We follow a similar approach as first described in [15,52]. In [15] it was shown that Pomeron exchange, i.e.…”
Section: Jhep11(2017)075mentioning
confidence: 99%
See 4 more Smart Citations
“…This argument has been extended to near-forward QCD scattering in AdS/CFT. We follow a similar approach as first described in [15,52]. In [15] it was shown that Pomeron exchange, i.e.…”
Section: Jhep11(2017)075mentioning
confidence: 99%
“…In [15,17] it was shown that this leads to the introduction of a "reggeized" AdS graviton known as the BPST pomeron; this pomeron serves as the leading contribution to the scattering in a unitarized treatment via an eikonal sum. This framework can also be extended to multi-particle near-forward scattering [52,77,78], which paves the way for the treatment of central inclusive production in section 4.…”
Section: Jhep11(2017)075mentioning
confidence: 99%
See 3 more Smart Citations